2022
DOI: 10.1371/journal.pone.0273819
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and common neurodevelopmental disorders—A scoping review

Abstract: Background A wealth of human and experimental studies document a causal and aggravating role of iron deficiency in neurodevelopmental disorders. While pre-, peri-, and early postnatal iron deficiency sets the stage for the risk of developing neurodevelopmental disorders, iron deficiency acquired at later ages aggravates pre-existing neurodevelopmental disorders. Yet, the association of iron deficiency and neurodevelopmental disorders in childhood and adolescence has not yet been explored comprehensively. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“… 39 Studies exploring relationships between infant and childhood iron deficiency and neurodevelopmental disorders such as autism spectrum disorder and attention deficit hyperactivity disorder have largely been correlative and have found inconsistent evidence of association. 40 Therefore, it will be valuable to follow the cohort to determine whether children born to women receiving ferric carboxymaltose have improved developmental trajectories and altered risk of neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Studies exploring relationships between infant and childhood iron deficiency and neurodevelopmental disorders such as autism spectrum disorder and attention deficit hyperactivity disorder have largely been correlative and have found inconsistent evidence of association. 40 Therefore, it will be valuable to follow the cohort to determine whether children born to women receiving ferric carboxymaltose have improved developmental trajectories and altered risk of neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…47 This is relevant to HG, as research has linked HG to adverse child neurological outcomes, 23,48 which has been hypothesised to be due to nutritional factors. However, it is not known whether this is due to basic malnutrition caused by a basic lack of energy (calorie intake) or if it is more specifically linked to particular micronutrients of concern, known to be linked to child cognitive and neurodevelopment (e.g., iodine, iron [49][50][51][52] ). Better characterisation of nutritional intake throughout pregnancy, linked to long-term follow-up of offspring, would allow this to be further explored and reduce reliance on retrospective studies, which may be subject to bias.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review reported that three studies found statistical evidence for an association between iron deficiency and ASD severity, while three studies did not. Further contradictory results were reported in studies investigating the prevalence of iron deficiency and iron deficiency anemia [ 207 ]. A study demonstrated that hemoglobin levels were significantly lower in ASD patients with intellectual disabilities and severe ASD [ 208 ].…”
Section: Mineralsmentioning
confidence: 99%